MOOCs, disruptive innovation and the future of higher education: A conceptual analysis. Issue 3 (4th May 2019) - Al-Imarah, Ahmed A.; Shields, Robin
Abstract: The potential influence of Massive Open Online Courses (MOOCs) on higher education institutions is much discussed and debated, with some arguing that MOOCs are a disruptive innovation that will radically change existing models of higher education. However, analyses of whether and how MOOCs might disrupt higher education models are relatively scarce. This paper analyses whether MOOCs should be considered a disruptive innovation according to the concept's defining criteria. It compares characteristics of disruptive innovation with current developments in MOOCs, suggesting three perspectives – performance, benefits, and market – that can be used as a lens and analytic framework to explore and evaluate current practice. The findings indicate that MOOCs do not match all the characteristics of disruptive innovation as they are commonly identified in the literature. However, MOOCs may be a sustaining innovation that establishes new markets for learners who are not served by universities.